Pengaruh Perbandingan Tepung Ubi Jalar Ungu (Ipomoea batatas L.) dan Tepung Beras (Oryza sativa L.) terhadap Karakteristik Kue Putu Mayang - Davita Putri, Ni Putu Amanda; Permana, I Dewa Gde Mayun; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Putu mayang cake is a traditional Indonesian snack originating from the Betawi. In general, putu mayang cakes are made from rice flour, but in terms of its benefits it is still lacking, so it is necessary to add other raw materials such as purple sweet potato. Purple sweet potato contains high fiber, and contains anthocyanin which acts as an antioxidant. The aim of this study was to determine the effect of the ratio of purple sweet potato flour to rice flour on the characteristics of putu mayang cakes, and to determine the best characteristics of putu mayang cakes. This study used a randomized block design (RBD) with 6 levels of treatment between of purple sweet potato flour and rice flour, namely P0 (0%:100%), P1 (4%:96%), P2 (8%:92%), P3 (12%:88%), P4 (16%:84%), P5 (20%:80%). Each treatment was repeated 3 times to obtain 18 experimental units. The data obtained will then be analyzed using ANOVA, and if it has a significant effect then it will be continued with Duncan's multiple range test. Based on the results of the comparison of purple sweet potato flour and rice flour on the characteristics of putu mayang cake. The best physicochemical characteristics in the treatment with a ratio of purple sweet potato flour (TUU) and rice flour (TB) were (12% TUU: 88% TB). The resulting characteristics are moisture content 51.79%, ash content 0.72%, crude fiber content 2.87%, total anthocyanin 1,89 mg/100g, antioxidant activity 27.20%, total phenol 0,73 mg/100mg, elasticity 19.39% , color test (L* 59.70; a* 11.37; b*-12.40), rather like color, rather like taste, rather like texture, slightly chewy texture intensity, and rather like overall acceptance.